Individual motivations, motivational climate, enjoyment, and physical competence perceptions in Finnish team sport athletes: A prospective and retrospective study - Zanatta, T.; Rottensteiner, C.; Konttinen, N.; Lochbaum, M. (Sports, 2018)
Despite the high rates of participation in sports clubs among Finnish youth, only a few reach elite levels. This study investigated a number of motivational factors, enjoyment, and perceived physical competence perceptions of Finnish youth athletes in their adolescence and then four years later to help understand determinants of elite level attainment. The sample consisted of 824 young athletes born in 1995, who were playing soccer, ice hockey, or basketball in the Finnish sports club system. As youths, participants completed measurements of the perceived task and ego climates, task and ego goal orientations, autonomous and controlled motivations, amotivation, sport enjoyment, and perceived physical competence. Retrospectively, the same participants completed measurements of task, ego, social relatedness, and autonomy supportive climates four years later. All variables were compared to self-reported elite status attainment. Additionally, we examined some demographic characteristics. Prospectively, the self-reported elite athletes (n = 79) reported significantly (p < 0.05) higher perceptions of a task climate, perceived physical competence, sport enjoyment, and autonomous motivation and a lower level of amotivation compared to nonelite athletes. The meaningfulness (Hedges` g) of the significant differences ranged from small to moderate. Retrospectively, elite athletes indicated significantly (p < 0.05) higher perception of a task climate and a social relatedness climate during their sporting career. Hedges` g ranged from moderate to large in meaningfulness. The findings highlighted the importance of focusing on the positive aspects surrounding elite athletes` perceptions to promote youth athletes` development, while not discounting the importance of physical size and talent.